An STM/STS study of site-selective adsorption of C70 molecules onto arc-shaped BODIPY molecular-networks. Issue 7 (2nd February 2017) - Xu, Jing; Liu, Wenxu; Geng, Yanfang; Deng, Ke; Zhan, Chuanlang; Zeng, Qingdao
Abstract : An STM/STS study of H-T-BO and C70 fullerene molecules self-assembly. Abstract : In this article, a donor–acceptor H-T-BO/C70 system was studied by a STM/STS method on the molecular level. STM results revealed that H-T-BO, a BODIPY-based derivative, can form a semi-closed molecular network at the 1-phenyloctane/HOPG interface. After introducing C70 fullerene molecules into the network, two kinds of self-assembled nanoarrays were observed by STM. Density functional theory has been utilized to reveal the formation mechanism of the molecular nanoarrays. Scanning Tunneling Spectroscopy (STS) measurements were performed to investigate the electronic properties of H-T-BO/C70 systems. I – V spectra combined with theoretical analyses showed that the introduction of C70 into the H-T-BO system induced a great drop of the band gap, which should be a result of electrons transferring from the donor H-T-BO to the acceptor C70 molecules.